Desain Layout Laboratorium Pneumatik Hidrolik Berbasis Line Produksi Untuk Meningkatkan Skill Otomasi di Era Industri 4.0 - Imam Sukoco; Rizki Setiadi; R. Ambar Kuntoro Mursid Gendroyono (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
The laboratory is a means of student learning in improving competence. Competence is one of the important elements in determining the quality of human resources, especially in facing challenges in the era of the industrial revolution 4.0 which relies entirely on technology and speed. This study aims to design a production line-based Pneumatic Hydraulic Laboratory to improve the automation skills of students majoring in mechanical engineering in the industrial era 4.0. The method in this study uses descriptive quantitative research. Collecting data through observation, design, pretest and posttest. The analysis uses descriptive statistics to describe the results of improving student skills. Based on the results of the study, it can be concluded that a production line-based laboratory layout design is indispensable in the era of the industrial revolution 4.0. The planned production design in the study is an automation system for drilling, pressing, conveyor, pick and place robots with PLC and HMI, the application of layout design can increase the average value of automation knowledge and skills (programming and automation simulation). The increase in the average value of knowledge is 22.72%. Meanwhile, the increase in automation competence was 29.23%.